What can universities do to support all their students to progress successfully throughout their time at university?. (3rd July 2017) - Mountford-Zimdars, Anna; Sanders, John; Moore, Joanne; Sabri, Duna; Jones, Steven; Higham, Louise
ABSTRACT: This article reviews the findings from a UK nationwide project on the causes of differences in student outcomes in higher education. The project was commissioned by the Higher Education Funding Council for England and reported in July 2015. We found that universities with an embedded, institution-wide approach that engaged senior managers, academic staff, professional service staff and students as stakeholders and agents in the differential outcomes agenda were most promising in decreasing progression gaps. Universities use targeted and universal interventions to affect change. Initiatives that tackle assessment and the content and meaning of curricula are a promising stream of interventions. Overall, more evaluations on what works and sharing of practice will further enable the sector to support all higher education students in reaching their academic potential.